Ostracism Reduces Reliance on Poor Advice from Others during Decision Making. (12th June 2015) - Byrne, Kaileigh A.; Tibbett, Thomas P.; Laserna, Lauren N.; Carter‐Sowell, Adrienne R.; Worthy, Darrell A.
Abstract: Decision making is rarely context‐free, and often, both social information and non‐social information are weighed into one's decisions. Incorporating information into a decision can be influenced by previous experiences. Ostracism has extensive effects, including taxing cognitive resources and increasing social monitoring. In decision making situations, individuals are often faced with both objective and social information and must choose which information to include or filter out. How will ostracism affect the reliance on objective and social information during decision making? Participants ( N = 245) in Experiment 1 were randomly assigned to be included or ostracized in a standardized, group task. They then performed a dynamic decision making task that involved the presentation of either non‐social (i.e. biased reward feedback) or social (i.e., poor advice from a previous participant) misleading information. In Experiment 2, participants ( N = 105) completed either the ostracism non‐social condition or social misleading information condition with explicit instructions stating that the advice given was from an individual who did not partake in the group task. Ostracized individuals relied more on non‐social misleading information and performed worse than included individuals. However, ostracized individuals discounted misleading social information and outperformed included individuals. Results of Experiment 2 replicated the findings of Experiment 1. Across two experiments, ostracized individuals were more critical of advice from others, both individuals who may have ostracized them and unrelated individuals. In other words, compared with included individuals, ostracized individuals underweighted advice from another individual but overweighed non‐social information during decision making. We conclude that when deceptive objective information is present, ostracism results in disadvantageous decision making. Copyright © 2015 John Wiley & Sons, Ltd.